KONFLIK DAN KOLABORASI SAINS AGAMA: MENYATUKAN CARA BERPIKIR ILMIAH DAN KEYAKINAN - Anjani, Nala; Nurul Laela, Faedah; Rifiansyah, Naufal; Nur Rofida, Silvina (Islamic Studies Journal for Social Transformation, 2024)
This study explores the relationship between science and religion, often perceived as discordant, leading to conflicts with negative societal impacts. The research aims to investigate various forms of conflict and collaboration between science and religion, seeking an integrative model that harmoniously unites both. Employing a qualitative descriptive approach through literature review, the findings indicate that conflicts can be mitigated through dialogue and cooperation. This research contributes to developing an integration framework applicable across various life aspects. Ultimately, science and religion can complement each other through integrative education and social practices, fostering a more harmonious and balanced society. This study enhances understanding of positive interactions between science and religion, promoting mutual enrichment.